Light acclimation strategies change from summer green to spring ephemeral as wild‐leek plants age. Issue 5 (13th May 2016) - Dion, Pierre‐Paul; Brisson, Jacques; Fontaine, Bastien; Lapointe, Line
Abstract : PREMISE OF THE STUDY: Spring‐ephemeral forest‐herbs emerge early to take advantage of the high‐light conditions preceding canopy closure; they complete their life cycle in a few weeks, then senesce as the tree canopy closes. Summer greens acclimate their leaves to shade and thus manage to maintain a net carbon gain throughout summer. Differences in phenology among life stages within a species have been reported in tree saplings, whose leaf activity may extend beyond the period of shade conditions caused by mature trees. Similar phenological acclimation has seldom been studied in forest herbs. METHODS: We compared wild‐leek bulb growth and leaf phenology among plants from seedling to maturity and from under 4 to 60% natural light availability. We also compared leaf chlorophyll content and chl a/b ratio among seedlings and adult plants in a natural population as an indicator of photosynthetic capacity and acclimation to light environment. KEY RESULTS: Overall, younger plants senesced later than mature ones. Increasing light availability delayed senescence in mature plants, while hastening seedling senescence. In natural populations, only seedlings acclimated to the natural reduction in light availability through time. CONCLUSIONS: Wild‐leek seedlings exhibit a summer‐green phenology, whereas mature plants behave as true spring ephemerals. Growth appears to be more source‐limited in seedlings than in mature plants. This modulation of phenological strategy, if confirmed in other species, would require a review of the current classification of species as either spring ephemerals, summer greens, wintergreens, or evergreens.